Postpartum Amenorrhoea among Manipuri Women: A Survival Analysis - Singh, N Sanajaoba; Singh, N Sharat; Narendra, RK (Journal of Health, Population and Nutrition, 2012)
Among the three major components of a closed birth interval, waiting time to conception can somehow be managed with effective contraceptives while gestation is universally constant in its duration; the duration of postpartum amenorrhoea (PPA) varies in complex nature. The present study aimed to investigate the proximate factors influencing the duration of PPA. A community-based, cross-sectional study was conducted in four valley districts of Manipur, India, during 1 August?31 December 2009, to analyze the differentials and determinants of duration of PPA, applying the survival analysis technique. In total, 1,225 ever-married women were selected through two-stage cluster sampling. The median duration of PPA was 5.7 months. Among the 11 explanatory variables of interest, only three variablesplace of residence (p<0.05), infant mortality from preceding pregnancy (p<0.01), and duration of breastfeeding (p<0.01) had a significant effect on the duration of PPA. The findings may be used as baseline information for future researchers and maternal health policy-makers. DOI: http://dx.doi.org/10.3329/jhpn.v30i1.11288 J HEALTH POPUL NUTR 2012 Mar;30(1):93-98